UZBEK SSR POLITICAL ELITE: SCIENCE AND SCHOLARSHIP IN THE REPUBLIC DURING THE LEADERSHIP OF NURIDDIN MUKHITDINOV - Feruz Boboyev (Western European Studies, 2025)
This article analyzes the changes in the field of science in the republic during the reign of Nuriddin Mukhitdinov, the first politician of the Uzbek SSR. The article also highlights a brief biography of Nuriddin Mukhitdinov, the process of justifying the victims of repression, the creation of new research institutes in the Uzbek SSR, issues related to the activities of the Academy of Sciences.
Keywords: Uzbek SSR; politician; first secretary; Academy of Sciences